2017
DOI: 10.1016/j.ijid.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Febrile rhabdomyolysis of unknown origin in refugees coming from West Africa through the Mediterranean

Abstract: The long incubation period does not support a mechanical cause of rhabdomyolysis. Furthermore, viral infections such as those caused by coxsackievirus are rarely associated with such a severe clinical presentation. It is hypothesized that other predisposing conditions like genetic factors, unknown infections, or unreported non-conventional remedies may be involved. Targeted surveillance of rhabdomyolysis cases is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Silvia Odolini et al have recently reported 48 cases of severe febrile rhabdomyolysis in refugees arriving in Italy from West Africa and admitted to 12 centers from May 2014 to December 2016 (Odolini et al, 2017). We describe the experience in Vibo Valentia, Calabria, a region not covered in their report.…”
mentioning
confidence: 87%
“…Silvia Odolini et al have recently reported 48 cases of severe febrile rhabdomyolysis in refugees arriving in Italy from West Africa and admitted to 12 centers from May 2014 to December 2016 (Odolini et al, 2017). We describe the experience in Vibo Valentia, Calabria, a region not covered in their report.…”
mentioning
confidence: 87%
“…A recent multicentre retrospective observational study of cases of febrile rhabdomyolysis, conducted by Odolini et al 17 between May 2014 and December 2016 in 12 Italian centres describes 48 cases, mainly young males coming from Nigeria (58.3%). Infections were diagnosed in 16 (33.3%) cases (such us EBV, CMV and Coxsackie B virus); in the remaining cases, the aetiology was undefined.…”
Section: Global Health Problem Analysismentioning
confidence: 99%